A COLLABORATIVE KNOWLEDGE SHARING MODEL FOR STAKEHOLDER-DRIVEN DIGITAL KNOWLEDGE PORTALS IN PADDY FARMING - Mat Yamin, Fadhilah; Wan Ishak, Wan Hussain; Abu, Noor Hidayah; Othman, Zakirah; Suroso, Arif Imam; Dewi, Febriantina; Rizky, Lokita; Kamilla, Khariyah; Tandra, Hansen (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
Knowledge sharing within paddy farming ecosystems remains constrained by fragmented information sources, limited accessibility, and weak coordination among stakeholders. While various digital agricultural platforms have been introduced, many fail to achieve sustained adoption due to unclear stakeholder roles and insufficient mechanisms for collaborative knowledge exchange. This study develops a Collaborative Knowledge Sharing Model (CKSM) to support stakeholder-driven digital knowledge portals for paddy farming. The research adopts a Design Science Research (DSR) approach involving problem identification, systematic literature analysis, stakeholder consultations, model development, and validation. Empirical insights were obtained through consultations with key agricultural organizations in Kedah, Malaysia, including the Kedah Department of Agriculture, the Muda Agricultural Development Authority (MADA), and Lembaga Zakat Negeri Kedah (LZNK), ensuring the contextual relevance of the model. The proposed CKSM consists of three integrated components: the Central Knowledge Hub (CKH) for structured knowledge storage and dissemination, the Stakeholder Collaboration Layer (SCL) for facilitating multi-stakeholder interaction and co-creation of knowledge, and the Monitoring and Feedback Mechanism (MFM) for continuous evaluation and improvement. Within a collaborative knowledge ecosystem, the proposed model also defines the roles of six stakeholder groups: farmers, agricultural agencies, research institutions, financial institutions, agri-tech providers, and community organizations. By integrating digital infrastructure with clearly defined governance and participation mechanisms, CKSM enhances knowledge accessibility, coordination, and collective learning within the paddy farming sector. The model provides a scalable framework for developing inclusive agricultural knowledge systems and supporting evidence-based decision-making in digital agriculture initiatives.